Differences in Medical Risk Factors and Lifestyles between People with and without Arterial Hypertension - Castillo Ayuso , R. (Consorcio de Universidades Mexicanas A.C., 2012)
The present report studied the differences between people with and without diagnosis of Hypertension (HT), in their Medical Risk Factors (MRF), Lifestyle (LS) and levels of Anger. It was applied the MRF and LS Questionnaire , developed for this research, it was taken anthropometric measures to a purposely selected sample of 246 subjects entitled to a private health system from Yucatan, with an age range of 25-65 years (=44.30 y σ= 10.66) of which 35.4% were male and 64.6% were women. Statistically significant association were found between diagnosis of Hypertension, Diabetes (X2 (1)= 14.05, p ≤ 0.05) and presence of Family Hypertension (X2 (1) = 7.73, p ≤ 0.05). Variables LS and other MRF behaved similarly in groups of people with Hypertension and without it. It’s possible that LS function as Hypertension exacerbating and not as causal agents. Even HT and Diabetes are closing relational; it does not seem to be a hereditary link between them.